2016
DOI: 10.1002/hed.24603
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound‐guided fine‐needle aspiration performed by surgeons newly trained in thyroid ultrasound

Abstract: The efficacy of ultrasound-guided FNAs performed by our 2 surgeons was similar to that of our radiologist. © 2016 Wiley Periodicals, Inc. Head Neck 39: 439-442, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…No differences in nodule characteristics were observed between radiologists and surgeons. Graciano et al (7) also found that the adequacy rate obtained by surgeons newly trained in thyroid ultrasound was similar to that obtained by one experienced radiologist. These findings suggest that patients with suspicious thyroid nodules may be evaluated by head and neck surgeons who perform ultrasound-guided FNA as well as radiologists.…”
Section: Discussionmentioning
confidence: 53%
“…No differences in nodule characteristics were observed between radiologists and surgeons. Graciano et al (7) also found that the adequacy rate obtained by surgeons newly trained in thyroid ultrasound was similar to that obtained by one experienced radiologist. These findings suggest that patients with suspicious thyroid nodules may be evaluated by head and neck surgeons who perform ultrasound-guided FNA as well as radiologists.…”
Section: Discussionmentioning
confidence: 53%
“…Although traditionally performed by radiologists, thyroid FNA has been successfully acquired by surgeons. A number of studies have confirmed an equivalency of the results when compared with those of radiologists (6,7,21). In a study performed by Al-Azawi et al (8), the inadequacy rate of thyroid FNAs done by radiologists versus surgeons was 9.3 % and 5.3 %, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…Oltmann et al found that surgeons documented lymph node status more often than radiologists and that surgeon-performed US patients had less disease recurrence (0% versus 12%, p = 0.01) [ 56 ]. With respect to ultrasound-guided thyroid fine-needle aspiration (FNA), Graciano et al reported no difference in efficacy when performed by radiologists or non-radiologists [ 57 ]. Other studies demonstrate that experience greater than seven years increases the positive predictive value and confidence of LNM detection [ 58 ].…”
Section: Discussionmentioning
confidence: 99%